On generalized Euler constants - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2002)
The generalized Euler constants are defined by formulas γ(r, k) = limx → ∞ ∑0 < n ≤ x; n ≡ r(mod k) ⅟n - ⅟k log x. The explicit formula for γ(r, k) is obtained applying the method of contour integration.